Literature Study: The Influence Of The Project Based Learning Model On Science Process Skills And Students' Creative Thinking Skills On Fluid Materials - Syifa Ramadhani; Joni Rokhmat; Denune Galang Prawira (International Journal of Contextual Science Education, 2026)
This study aims to analyze the influence of the project-based learning (PjBL) model on science process skills and students' creative thinking abilities in fluid materials through a literature study approach and bibliometric analysis. Data were collected using the Publish or Perish application with the keywords "project based learning", "science process skills", "creative thinking skills", and "fluids". The search results produced a number of articles which were then screened based on relevance and eligibility criteria. The inclusion criteria consisted of: (1) articles published in peer-reviewed journals, (2) studies focusing on the implementation of the PjBL model in science or physics learning, (3) research discussing science process skills and/or creative thinking skills, and (4) publications available in the last ten years and written in English. Based on these criteria, 20 main articles were selected for further analysis. Bibliometric analysis was conducted using the VOSviewer application to map research trends, relationships between topics, and the development of publications related to PjBL in physics learning. The results show that the PjBL model is consistently reported to improve students' science process skills and creative thinking skills, particularly in fluid materials. This model encourages active student engagement through project activities, contextual problem-solving, and collaboration, thereby positively influencing conceptual understanding and the development of 21st-century skills. The novelty of this study lies in the integration of a systematic literature review with bibliometric analysis to comprehensively map the research landscape of PjBL related to science process skills and creative thinking in fluid learning. This approach not only synthesizes empirical findings but also identifies research trends and thematic relationships, providing a clearer direction for future studies in physics education.